Lugra saree worn by Koli women - Mumbai Archive Project Team (Jio Institute, 2024)
The Lugra saree is draped in a manner suited for the active lifestyle of Koli women. It is wrapped around the waist with pleats tucked in the front, allowing ease of movement during outdoor work. The khadki, a white scarf, or dupatta, completes the attire and is worn over the upper body.